Strategies for the adoption of innovation processes in agricultural productive units of the department of La Guajira – Colombia: literary review and systemic approach (2023)
From the appearance of man to the present, food production has been a critical issue in ensuringthe survival of the human species. Over the centuries, agricultural production has evolved with the domestication of plant and animal species and the emergenceof technologies and techniques in production processes, affecting population growthand cities. The research seeks to describe the strategies for adopting innovation processes in the Department of La Guajira -Colombia agricultural production units.The results show that, in the last four decades, innovation strategies have begun to be discussed as a term that has evolved, going from incorporating new technologies to including elements related to efficiency, economic sustainability, sustainability, redesign of organizational structures, and the implementation of best practices that result in quality, quantity, safety and hygiene of agricultural activities. It is concluded that the studies on innovation strategies in agricultural productive units can be about phenomena that promote agricultural innovation, agricultural production models,and improvements in agricultural production processes, of which there is evidence of application in the Department of La Guajira